2020
DOI: 10.3390/bs10020054
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in the Social World of College Students: Bridging Interpersonal Stress and Fear of Missing Out with Mental Health

Abstract: Introduction: The college years are characterized by psychosocial and biological phenomena that may impact mental health, such as heightened sensitivity to social stressors and compromises in sleep quantity and quality. The current study uses a biopsychosocial approach to examine the associations among interpersonal stress, Fear of Missing Out (FoMO), insomnia, and mental health. Methods: Survey data were collected from 283 undergraduate students (90% female) with a mean age of 21.4 years. A path analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 41 publications
2
28
0
9
Order By: Relevance
“…Recent studies show that FOMO is related to perceived stress (Adams et al, 2020;Elhai et al, 2018). The FOMOstress relationship is also consistent with SDT, and with FOMO as a response to negative affectivity, which fits within I-PACE.…”
Section: Hypothesessupporting
confidence: 73%
See 1 more Smart Citation
“…Recent studies show that FOMO is related to perceived stress (Adams et al, 2020;Elhai et al, 2018). The FOMOstress relationship is also consistent with SDT, and with FOMO as a response to negative affectivity, which fits within I-PACE.…”
Section: Hypothesessupporting
confidence: 73%
“…Furthermore, FOMO has shown small-to-medium positive associations with depression symptom severity and medium-to-large relationships with anxiety severity (Dempsey et al, 2019;Dhir, Yossatorn, Kaur, & Chen, 2018;Elhai et al, 2018;Elhai, Yang, Fang, Bai, & Hall, 2020). Additionally, FOMO demonstrates large positive correlations with perceived stress (Adams, Murdock, Daly-Cano, & Rose, 2020;Elhai et al, 2018). These findings have been revealed in studies spanning numerous parts of the world, including North and South America, Europe, and Asia .…”
mentioning
confidence: 76%
“…Although, some scholars argue that the relationship between sleep quality and affect may be bidirectional ( 74 76 ), previous research has also shown that both positive and negative affect can mediate the impact of expressive suppression on sleep quality ( 73 , 77 ). Another recent study showed that insomnia partially mediated a significant association of interpersonal stress and FoMO with mental health ( 78 ). Moreover, the relationship between negative affect and sleep quality may also be mediated by smartphone addiction ( 79 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the concurrent validity of Przybylski’s FoMO scale, previous studies have found that FoMO is not only positively associated with online problematic behaviors, such as social media disorder [ 22 ], smartphone addiction [ 23 ], and problematic internet use [ 14 ], but also has associated with psychopathological symptoms [ 24 ] and leads to negative consequences such as more phubbing behavior [ 2 ], poorer academic performance [ 25 ], more sleep problems [ 26 ], and lower well-being [ 27 ]. Therefore, it was expected that FoMO is positively associated with smartphone addiction but negatively associated with subjective well-being.…”
Section: Introductionmentioning
confidence: 99%